E-Learning dalam Pembuatan Miniatur Ekosistem untuk Melatih Keterampilan Proses Mahasiswa melalui Discovery Learning - Fatikhatun Nikmatus Sholihah; Primadya Anantyarta (Universitas Nusantara PGRI Kediri, 2021)
English translation. Basic ecology is a basic science that studies the relationship between living things and their environment. One of the ingredients in this course is the terrestrial ecosystem. Video process skills are one way used to teach the material during pandemics. The purpose of learning from this course is that students are able to carry out experiments (practicum) both in the laboratory and in the UNWAHA environment. The purpose of this research is to train students' process skills through discovey learning in creating miniature ecosystems through E-Learning. This study used a pre-experimental design. The research design used is the design of one group pretest-posttest, i.e. pretest before implementation and posttest after implementation. The instrument used in the form of a questionnaire of process skills is used to assess the results of learning in the form of video. The results showed that each individual's process skills could be known that 17 students got excellent grades and 4 good grades. Based on these results, it can be concluded that miniature ecosystems can train students' process skills.